(untitled) (Nigerian Journal of Technology, 2003)
In this paper a two-dimensional mathematical model of steady non-uniform water flow in open channels and shallow reservoirs is presented. The irrotational flow condition is used for simplification of the system of the governing shallow water equations and the final nonlinear differential equation is solved for the unknown energy head using the finite element method. A one - dimensional problem was solved with diffusion hydraulic model (DHM), energy diffusion hydraulic model (EDHM) and with one - dimensional model. The comparison of results indicates EDHM to be more accurate than D HM.